Analisa Penyebab Kerusakan Mesin Tenun dengan Menggunakan Integrasi FMEA, FTA, dan Age Replacement - Farhan Ramadhan; Indah Apriliana Sari W (KOLONI, 2026)
Weaving machines play a crucial role in ensuring the smooth running of the textile production process. Repeated machine failures can lead to decreased production output and increased downtime. This study aims to identify potential failures, analyze the root causes of weaving machine failures, and prioritize appropriate repairs. The methods used are Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) to identify failure modes and root causes of damage, as well as the Age Replacement method through the calculation of Mean Time Between Failure (MTBF) and Mean Time To Failure (MTTF) to analyze the level of machine reliability. Data were obtained from observations, interviews, and historical data of machine failures. The findings indicate that the shuttle, oil pump, and connecting rod are the most critical components of the weaving machine, as they recorded the highest Risk Priority Number (RPN) values of 360, 280, and 245, respectively. These results suggest that the three components should be given priority in maintenance planning. The analysis further revealed that their failures are primarily associated with component wear, excessive friction, poor lubricant quality, blockage within the lubrication system, excessive operating loads, high vibration levels, and improper component installation. Based on the Age Replacement analysis, the recommended preventive maintenance interval is 243 operating hours for repairable components and 87.4 operating hours for non-repairable components. Implementing these maintenance intervals is expected to reduce the frequency of machine failures, minimize downtime, and improve the overall reliability and operational performance of the weaving machine.